Decision Analysis of A Dual Channel Supply Chain Considering Manufacturer’s Online Returns and Online Reviews - Zhao, Huan-huan; Xia, Zhen-juan (International Journal of Industrial Engineering: Theory, Applications and Practice, 2024)
With the gradual development of online shopping, more and more consumers buy products online. The manufacturers who develop online channels often prioritize consumer online reviews. They implement measures such as return services to attract consumers and maximize profits. Online reviews and return service levels are important factors influencing consumers and the profits of the supply chain. To well analyze the impact of these two factors on the dual-channel supply chain, we establish some basic models with the manufacturer’s online return service and online reviews. Then, we analyze optimal decisions under either decentralized or centralized decision-making scenarios. The impact of online review and return service levels on optimal supply chain decisions and profits are further analyzed. Finally, based on the developed model, a revenue-sharing contract coordination scheme is designed to achieve Pareto improvements in the supply chain. The results show that, in any case, the profit gap between centralized and decentralized decision-making increases as the return rate increases. The return rate does not have a linear impact on the profits of manufacturers and retailers, but when the return rate is greater than 0.85, it seriously jeopardizes the interests of manufacturers. In addition, the level of return service has less impact on the supply chain than the perceived quality of online reviews. The overall profit of the supply chain under centralized decision-making is significantly greater than that under decentralized decision-making, and the coordination model can effectively coordinate the supply chain and alleviate conflicts.